Enzymatic debridement in geriatric burn patients: a reliable option for selective eschar removal - Tapking, Christian; Rontoyanni, Victoria G.; Diehm, Yannick; Strübing, Felix; Solimani, Farzan; Bigdeli, Amir Khosrow; Hundeshagen, Gabriel; Fischer, Sebastian; Kneser, Ulrich; Siegwart, Laura (Journal of Clinical Medicine, 2023)
The treatment of geriatric burn patients represents a major challenge in burn care. The objective of this study was to evaluate the efficacy of enzymatic debridement (ED) in geriatric burn patients. Adult patients who received ED for treatment of mixed pattern and full thickness burns (August 2017-October 2022) were included in this study and grouped in the younger (18-65 years) and geriatric (≥65 years) groups. Primary outcome was a necessity of surgery subsequent to ED. Both groups (patient characteristics, surgical and non-surgical treatment) were compared. Multiple logistic and linear regression models were used to identify the effect of age on the outcomes. A total of 169 patients were included (younger group: 135 patients, geriatric group: 34 patients). The burn size as indicated by %TBSA (24.2 ± 20.4% vs. 26.8 ± 17.1%, p = 0.499) was similar in both groups. The ASA (2.5 ± 1.1 vs. 3.4 ± 1.1, p < 0.001) and ABSI scores (6.1 ± 2.8 vs. 8.6 ± 2.3, p < 0.001) were significantly higher in the geriatric group. The %TBSA treated with ED (5.4 ± 5.0% vs. 4.4 ± 4.3%, p = 0.245) were similar in both groups. The necessity of additional surgical interventions (63.0 % vs. 58.8 %, p = 0.763) and the wound size debrided and grafted (2.9 ± 3.5% vs. 2.2 ± 2.1%; p = 0.301) were similar in both groups. Regression models yielded that age did not have an effect on efficacy of ED. We showed that ED is reliable and safe to use in geriatric patients. Age did not have a significant influence on the surgical outcomes of ED. In both groups, the size of the grafted area was reduced and, in many patients, surgery was avoided completely.